A Potential New Human Pathogen Belonging to Helicobacter Genus, Identified in a Bloodstream Infection - van der Mee-Marquet, Nathalie L.; Bénéjat, Lucie; Diene, Seydina M.; Lemaignen, Adrien; Gaïa, Nadia; Smet, Annemieke; Haesebrouck, Freddy; Cherkaoui, Abdessalam; Ducournau, Astrid; Lacomme, Sabrina; Gontier, Etienne; Bernard, Louis; et al. (Frontiers in Microbiology, 2017)
We isolated from aerobic and anaerobic blood culture bottles from a febrile patient, a Helicobacter-like Gram negative, rod-shaped bacterium that MALDI-TOF MS failed to identify. Blood agar cultures incubated in a microaerobic atmosphere revealed a motile Gram negative rod, which was oxidase, catalase, nitrate reductase, esterase, and alkaline phosphatase positive. It grew at 42°C with no detectable urease activity. Antimicrobial susceptibility testing showed that the organism was susceptible to beta-lactams, gentamicin, erythromycin and tetracycline but resistant to ciprofloxacin. Electronic microscopy analysis revealed a 3 X 0.5 µm curved rod bacterium harboring 2 sheathed amphitrichous flagella. Whole genome sequencing revealed a genome 1,708,265 base-pairs long with a GC content of 37.80% and a total of 1,697 coding sequences. The genomic analyses using the nucleotide sequences of the 16S rRNA gene, hsp60 and gyrB genes, as well as the GyrA protein sequence, and the results of Average Nucleotide Identity and in silico DNA-DNA hybridization suggest/offer evidence for a novel Helicobacter species close to Helicobacter equorum and belonging to the group of enterohepatic Helicobacter species. As soon as the particular peptide mass fingerprint of this pathogen is added to the spectral databases, MALDI-TOF MS technology will improve its identification from clinical specimens, especially in case of “sterile infection”. and likely allow the proposal of a new species “Helicobacter caesarodunensis”, with respect to the Latin name of the place of isolation, Caesarodunum (Tours, France). We propose to associate the present strain with the Latin name of the place of isolation; Caesarodunum (Tours, France) and suggest “Helicobacter caesarodunensis” for further description of this new bacterium.